SUDUT-SUDUT BERELASI DENGAN GRAFIK FUNGSI SINUS DAN COSINUS - Tamurih (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2016)
Trigonometry is the uppermost group of the most difficult materials collection in mathematics. Trigonometry is belonging to the materials that have the greatest number of concept even trigonometry is well known by the quantity of formula or identity and application from trigonometry. They are establish that trigonometry is a very important material. In fact, the majority of students which dislike the trigonometry and they have low mark even the lowest from another topics in mathematics. The main factor is the teacher. The teacher is lack innovative  in  teaching  trigonometry material even the difficulties degree of trigonometry material same with the difficulties degree of the students which receive the material from their teacher. In order  that, the writer  try to  give  an  idea which can be an alternative in teaching learning trigonometry, especially angles relations   which   have   tens   of   angles relations. In determine the angles relations each quadrant, it can using the graph functions of sinus and cosines. It means that the graphs method can be an alternative in teaching learning trigonometry, especially angles relations.